2020
DOI: 10.1084/jem.20191548
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of nonstructural protein 1 in dengue pathogenesis

Abstract: Dengue is a major public health concern in the tropical and subtropical world, with no effective treatment. The controversial live attenuated virus vaccine Dengvaxia has boosted the pursuit of subunit vaccine approaches, and nonstructural protein 1 (NS1) has recently emerged as a promising candidate. However, we found that NS1 immunization or passive transfer of NS1 antibodies failed to confer protection in symptomatic dengue mouse models using two non–mouse-adapted DENV2 strains that are highly virulent. Exog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 72 publications
1
33
0
Order By: Relevance
“…Subsequent studies using non-mouse adapted, mouse-virulent DENV2 strains (D2Y98P and EHIE2862Y15) found that secreted NS1 did not have a strong pathogenic role, nor did NS1 immunity confer protection in interferon αβ receptor knockout (A129) and interferon αβγ receptor knockout (AG129) mice. This is hypothesized to occur because the virulence of these strains relies on their structural components [41]. It is suggested that the role of NS1 in pathogenesis is strain-dependent, so NS1 may not be well suited as the universal vaccine immunogen for DENV.…”
Section: Role Of Ns1 In Dengue Pathogenesismentioning
confidence: 99%
“…Subsequent studies using non-mouse adapted, mouse-virulent DENV2 strains (D2Y98P and EHIE2862Y15) found that secreted NS1 did not have a strong pathogenic role, nor did NS1 immunity confer protection in interferon αβ receptor knockout (A129) and interferon αβγ receptor knockout (AG129) mice. This is hypothesized to occur because the virulence of these strains relies on their structural components [41]. It is suggested that the role of NS1 in pathogenesis is strain-dependent, so NS1 may not be well suited as the universal vaccine immunogen for DENV.…”
Section: Role Of Ns1 In Dengue Pathogenesismentioning
confidence: 99%
“…The presence of NS1 antibodies correlates with lower disease severity in dengue patients [5,27], and robust protection against DENVinduced hemorrhage, coagulopathy, viremia, and mortality [27,28]. However, the development of anti-NS1 therapies to weaken DENV severity has recently been challenged, as researchers found that the pathogenic role of NS1 is DENV strain dependent [29], and the potency of DENV NS1 to permeate the NVU has been shown to be much less effective than the NS1 protein of another Flaviviridae member WNV [30]. WNV being a 'true' neurotropic virus, one could envision to use anti-WNV NS1 antibodies to treat WNV-induced encephalitis.…”
Section: Trends In Molecular Medicinementioning
confidence: 99%
“…Although the LP is an effective mechanism to limit infection, DENV has developed strategies to protect itself from a lectin-mediated attack ( Table 1 and Figure 2 B). DENV produces a nonstructural protein (NS1) to assist in intracellular viral replication [ 98 , 99 ], enhance dengue infection [ 100 , 101 , 102 ] and modulate the endothelial hyperpermeability, potentially to disseminate infections [ 103 , 104 , 105 , 106 ], which could further contribute to dengue pathogenesis [ 99 , 107 ]. NS1 is a glycoprotein that can be detected as intracellular, surface membrane-associated and secreted forms [ 45 , 99 ].…”
Section: Lectin Pathway In Denguementioning
confidence: 99%